2021
DOI: 10.20428/yjms.v15i1.1814
|View full text |Cite
|
Sign up to set email alerts
|

Anemia and Its Associated Factors among Final-Year Medical Students at Sana'a University, Yemen

Abstract: Objective: To determine the prevalence of anemia and its associated risk factors among final-year medical students at Sana'a University, Yemen. Methods: This cross-sectional study was conducted among 269 final year students randomly selected from the medical faculties of Sana'a University in the period from January to April 2018. Data were collected using a structured questionnaire, while venous blood samples were collected by venipuncture into EDTA tubes. Hemoglobin (Hb) concentration was estimated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
2
Order By: Relevance
“…The disagreement in the study findings could be due to the fact that the previous study had a small sample size of only 80 meanwhile the present study had a bigger sample size of 384 participants. On the contrary, the prevalence of anaemia found in the present study is higher compared to the results of a study in Yemen at Sana'a University which showed that anaemia was prevalent among 4.5% of medical students [29]. The discrepancy in the study findings could be because of the variation in study participants in that the previous study only sampled finalyear medical students whereas the present study sampled female undergraduate medical students.…”
Section: Yes 16%contrasting
confidence: 99%
See 1 more Smart Citation
“…The disagreement in the study findings could be due to the fact that the previous study had a small sample size of only 80 meanwhile the present study had a bigger sample size of 384 participants. On the contrary, the prevalence of anaemia found in the present study is higher compared to the results of a study in Yemen at Sana'a University which showed that anaemia was prevalent among 4.5% of medical students [29]. The discrepancy in the study findings could be because of the variation in study participants in that the previous study only sampled finalyear medical students whereas the present study sampled female undergraduate medical students.…”
Section: Yes 16%contrasting
confidence: 99%
“…Contrary to what was found in the present study, the results of a study conducted in Saudi Arabia, showed that there was no statistical association between anemia and age [32]. As well, Nassar et al [29] conducted their study and found no statistically significant association between anemia and age. The findings of the two previous studies are in disagreement with the results of the present study probably because the present study was conducted in a third world country.…”
Section: Social Demographic Factors Associated With Iron Deficiency A...contrasting
confidence: 99%